Estetika dalam surah Yusuf - Zulkarnain Mohamed, (Penerbit Universiti Kebangsaan Malaysia, 2003)
This study is concerned with aesthetic aspects of the quranic chapter of Yusuf. The main objective is to prove the strength of the concept of the most beautiful story as mentioned at the beginning of the chapter. Secondly, it is also aimed at analyzing the aesthetic aspects in order to be made a useful guideline for the writing of Islamic creative prose, i.e. novel, novellete and short story. Finally, it tries to introduce the concept of the creative writing in the present stream of postmodernism that is seeking the alternative truth in place of the uncertainty of virtue that has been related with the modernism stream. This study is based on theoretical criticism and development examinations of Islamic literature. Comparison method is also important to the study apart from its emphasis on influence or historical aspect that is concerned with the study case i.e., the chapter of Yusuf as the true model of Islamic creative prose. To conclude, the chapter of Yusuf can be regarded the true model for contemporary muslim writers and it is suitable to be introduced in the postmodernism stream